2004
DOI: 10.1159/000082933
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutation of the LKB1/STK11 Gene with Loss of the Normal Allele in an Aggressive Breast Cancer of Peutz-Jeghers Syndrome

Abstract: Peutz-Jeghers syndrome (PJS) is an autosomal-dominant polyposis disorder with an increased risk of multiple cancer. The LKB1/STK11 gene, which acts as a tumor suppressor, is responsible for PJS and plays a role in suppressing breast cancer. The low expression of LKB1/STK11 in sporadic breast cancer is significantly associated with shorter survival. Here we describe a PJS patient with aggressive breast cancer that carried not only a germline mutation of LKB1/STK11 but also loss of the normal allele. The combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 26 publications
2
23
0
2
Order By: Relevance
“…LKB1 has a tumor suppressor function in the human cancers, including breast cancer (5,6). In our previous study, we reported that overexpression of LKB1 protein in MDA-MB-435 cancer cells can result in growth inhibition, which is mediated by G 1 arrest and p21 WAF1/CIP1 induction, and low expression of the LKB1 protein in human breast cancer is significantly associated with a shorter survival (5).…”
Section: Introductionmentioning
confidence: 99%
“…LKB1 has a tumor suppressor function in the human cancers, including breast cancer (5,6). In our previous study, we reported that overexpression of LKB1 protein in MDA-MB-435 cancer cells can result in growth inhibition, which is mediated by G 1 arrest and p21 WAF1/CIP1 induction, and low expression of the LKB1 protein in human breast cancer is significantly associated with a shorter survival (5).…”
Section: Introductionmentioning
confidence: 99%
“…26 Moreover, many variants that were previously termed "variants of unknown significance" have since been more definitively categorized as deleterious or nondeleterious, and efforts are ongoing to understand the clinical implications of as many variants as possible.…”
Section: Ptenmentioning
confidence: 99%
“…Loss of heterozygosity of 19p13 was reported in various cancers including thyroid cancer, sex cord stromal tumors, breast cancer, oral carcinoma, prostate cancer, pancreas carcinoma, brain tumors, colorectal carcinoma, gynecological tumors, lung cancers and ovarian carcinoma [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Some of the studies included genetic analysis of STK11/LKB1 and showed mutation in a subset of tumors especially related with Peutz-Jeugher Syndrome such as breast, colorectal, lung, pancreatic, biliary and ovarian cancer [41][42][43][44][45][46][47][48][49]. On the other hand, quite a lot of studies reported mutations and/or loss or various alterations of BRG1 in human cancer lines and primary tumors [50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Roles Of Swi/snf Proteins In Cancermentioning
confidence: 99%